PERANCANGAN SISTEM PENGOLAHAN DATA DISTRIBUSI PRODUK OLAHAN MAKANAN LOKAL PADA TOKO ZIO-ZHILA BERBASIS WEB - Rimma Tota Simatupang; Imti Tsalil Amri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Zio-Zhila Store is a business engaged in distributing local processed food products to retail stores. The current distribution data processing system is still carried out manually using handwritten records and Microsoft Excel, which causes several problems such as slow data retrieval, repetitive data entry, data inconsistency, and lack of integration due to the absence of a centralized Database. This study aims to analyze the existing system and design a web-based distribution data processing system to improve the effectiveness and efficiency of data management at Zio-Zhila Store. The research methods used include observation, interviews, and Documentation, while the system development method applies the waterfall model consisting of requirement analysis, system design, coding, testing, and implementation stages. The system is developed using the PHP programming language and MySQL as the Database management system. The results of this study are a web-based distribution data processing application that facilitates faster, more accurate, and integrated data recording, retrieval, and report generation.Keywords: Design, Information System, Distribution Data Processing, Web